Поняття та сутність міжнародного конфлікту в науці про міжнародні відносини. - Шеренговский, Д.В.; Шеренговський, Д.В.; Sherengovskij, D. (My University, 2011)
The article analyzes the scientiﬁ c approaches to the deﬁ nition and understanding of international conﬂ ict in the Theory of International Relations. The classiﬁ cation of foreign and national scientists of interna- tional conﬂ icts, based on the criteria that constitute the main character-istics of international conﬂ icts is examined. The author draws attention to the structure of international conﬂ icts, conducting system perception of conﬂ ict and reﬂ ecting the inﬂ uence of the system of international rela- tions on the formation of conﬂ ict factors.
Шеренговський, Д.В. Поняття та сутність міжнародного конфлікту в науці про міжнародні відносини. / Д.В. Шеренговський // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 43. С. 98 - 108.
Keywords: Поняття та сутність міжнародного конфлікту; Міжнародні відносини; Міжнародні конфлікти в науці про міжнародні відносини; Класифікація міжнародних конфліктів; Классификация международных конфликтов; Международные конфликты в науке о международных отношениях; Международные отношения; Понятие и сущность международного конфликта; The concept and essence of international conflict; international relationships; International conflicts in the science of international relations; Classification of international conflicts